BIM as a tool to support the collaborative project between the structural engineer and the architect: BIM execution plan, education and promotional initiatives - Caires, Bruno Emanuel Araújo (2013)
Dissertação de mestrado integrado em Civil Engineering (área de especialização em Perfil de Estruturas e Geotecnia)